2003
DOI: 10.1051/rnd:2003012
|View full text |Cite
|
Sign up to set email alerts
|

Developmental competence of prepubertal goat oocytes selected with brilliant cresyl blue and matured with cysteamine supplementation

Abstract: -The aim of this study was to assess the effect of oocyte selection using the brilliant cresyl blue (BCB) test plus the addition of cysteamine to the in vitro maturation (IVM) medium to improve the in vitro embryo development of prepubertal goat oocytes. The oocytes were exposed to 26 µM BCB and classified according to their cytoplasm coloration: BCB+ (oocytes with blue cytoplasm) and BCB-(unstained oocytes). The oocytes were matured in a conventional IVM medium supplemented with cysteamine 100 µM. The control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
30
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 36 publications
8
30
1
1
Order By: Relevance
“…This confirmed previous reports that BCB+ oocytes presented higher normal fertilization and embryo development rates than BCB− oocytes in goats [35,45], cattle [17,36] and pigs [34]. This study also showed that the better cytoplasmic maturity and higher developmental potential of the BCB+ oocytes were correlated with their npg larger sizes, higher percentages of SN chromatin configuration and higher frequencies of early atresia in comparison with the BCB− oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…This confirmed previous reports that BCB+ oocytes presented higher normal fertilization and embryo development rates than BCB− oocytes in goats [35,45], cattle [17,36] and pigs [34]. This study also showed that the better cytoplasmic maturity and higher developmental potential of the BCB+ oocytes were correlated with their npg larger sizes, higher percentages of SN chromatin configuration and higher frequencies of early atresia in comparison with the BCB− oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…This implies that the BCB test is a useful tool for selection of more developmentally competent oocytes. These results are in agreement with similar studies in cattle (Pujol et al, 2004;Alm et al, 2005;Bhojwani et al, 2007), goat (Rodriguez-González et al, 2003;Kątska-Książkiewicz et al, 2007) and pig (Wongsrikeao et al, 2006). Selection of excellent quality oocytes is highly desirable for procedures involving extensive manipulations such as pronuclear microinjections, intracytoplasmic sperm injection, and nuclear transplantation, which requires high developmental competence after embryo transfer.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, non-invasive markers of oocyte quality that allow for accurate and fast selection prior to IVM have become of prime importance. It has been demonstrated that brilliant cresyl blue (BCB) can be used for the selection of competent oocytes in pig, goat and cattle (Rodriguez-González et al, 2003;Pujol et al, 2004;Alm et al, 2005;Wongsrikeao et al, 2006;Bhojwani et al, 2007;Kątska-Książkiewicz et al, 2007). Although it was previously shown that BCB staining is a useful tool for selecting more competent oocytes, the test is still not routinely included in laboratory selection protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of contrary reports [16,17], our experimental works [8,12,18] and other numerous reports [13,14,[19][20][21][22][23] demonstrate that there is no deleterious effect of the staining procedure on viability of the oocytes. This approach has successfully been used to identify oocytes that possess superior developmental capacity in mice [13] and some domestic animal species [14,20,23].…”
Section: Introductioncontrasting
confidence: 77%